2019
DOI: 10.1007/s00404-019-05174-0
|View full text |Cite
|
Sign up to set email alerts
|

Does the implementation of a restrictive episiotomy policy for operative deliveries increase the risk of obstetric anal sphincter injury?

Abstract: Does the implementation of a restrictive episiotomy policy for operative deliveries increase the risk of obstetric anal sphincter injury?. Abstract: 250 words 6 Main text: 3.054 words 7 8 ABSTRACT: 250 words 44 45 Purpose 46 Our main objective was to investigate whether the implementation of a restrictive 47 72 73 74 Title: Does the implementation of a restrictive episiotomy policy for operative deliveries 75 increase the risk of obstetric anal sphincter injury? 76 MAIN TEXT: 3.054 words 77 78

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Finally, the reduction that we observed between 2016 and 2017 boosted the general downward trend (rate of change of about − 20%), showing the potential impact of the national debate about episiotomy practice in France 29 , 44 . The reduction in the episiotomy rate deserves to be compared to the obstetric anal sphincter injuries (OASIS) rate considering that there is concern about an increase in OASIS associated with a decrease in episiotomies 4 , 9 , 28 , 45 48 . Based on our previous study 28 , we found that severe perineal tears (third and fourth degrees) significantly increased in women who had non-operative vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reduction that we observed between 2016 and 2017 boosted the general downward trend (rate of change of about − 20%), showing the potential impact of the national debate about episiotomy practice in France 29 , 44 . The reduction in the episiotomy rate deserves to be compared to the obstetric anal sphincter injuries (OASIS) rate considering that there is concern about an increase in OASIS associated with a decrease in episiotomies 4 , 9 , 28 , 45 48 . Based on our previous study 28 , we found that severe perineal tears (third and fourth degrees) significantly increased in women who had non-operative vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…A small pilot randomized trial failed to identify any significant preventive effect 9 . Although several retrospective studies, mainly European national cohort studies, have reported that mediolateral episiotomy has a protective effect against OASI 10 12 , these studies appear to have reported a high rate of episiotomy and a high rate of OASI in the few cases without episiotomy, which seem to be not concordant with French practices. In our country, the 2005 national guidelines recommended restricted use of episiotomy during vaginal delivery, including instrumental delivery 13 .…”
Section: Introductionmentioning
confidence: 91%
“…The results of observational studies are contradictory [ 10 – 20 ], and their conclusions may be limited owing to insufficient consideration of the confounding bias by indication. The implementation of a very restrictive episiotomy policy could even be associated with an increase in OASIs incidence during forceps delivery [ 21 ]. The major problem when evaluating OASIs is that maternal, fetal and medical characteristics are different in the episiotomy and no episiotomy groups.…”
Section: Introductionmentioning
confidence: 99%